Diagnosing Student Node Mastery: Impact of Varying Item Response Modeling Approaches - Embretson, Susan (Frontiers in Education, 2021)
An important feature of learning maps, such as Dynamic Learning Maps and Enhanced Learning Maps, is their ability to accommodate nation-wide specifications of standards, such as the Common Core State Standards (CCSS), within the map nodes along with relevant instruction. These features are especially useful for remedial instruction, given that accurate diagnosis is available. The year-end achievement tests are potentially useful in this regard. Unfortunately, the current use of total score or area sub-scores are either not sufficiently precise or not sufficiently reliable to diagnose mastery at the node level especially when students vary in their patterns of mastery. The current study examines varying approaches to using the year-end test for diagnosis. Prediction at the item level was obtained using parameters from varying IRT models. The results support using mixture class IRT models predicting mastery in which either items or node scores vary in difficulty for students in different latent classes. Not only did the mixture models fit better, but trait score reliability was maintained for the predictions of node mastery.